Enzymatic hydrolysis processing of soybean meal altered its structure and in vitro protein digestive dynamics in pigs - Wang, Dapeng; Du, Honglin; Dang, Xiuquan; Zhao, Yufei; Zhang, Jiaxuan; Liu, Rujie; Ge, Zhenying; Zhong, Qingzhen; Sun, Zewei (Frontiers in Veterinary Science, 2024)
IntroductionThe study evaluated the enzymatic hydrolysis processing on physicochemical properties and protein digestive dynamics of soybean meal (SBM), as well as the relationship between protein secondary structure and digestive parameters was established.MethodsScanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were employed to analyze the microstructure and protein structure of the SBM and enzymatic hydrolysis processed soybean meal (ESBM). SBM and ESBM were incubated with pepsin at pH 3.5 and 39°C for 30 min, then with pancreatin at pH 6.8 for 0–240 min. The in vitro protein digestive dynamics were described as the release dynamics of amino acids and low molecular weight peptides (AA_LMW).ResultsThe results showed that enzymatic hydrolysis processing did not alter the chemical composition of SBM, but changed its microstructure and protein structure. After enzymatic hydrolysis processing, the size of blocky structures of SBM decreased, exhibiting a fibrous surface and a relatively loose internal structure. The β-sheet content of ESBM was lower than that of SBM (p < 0.05), while the α-helix, β-turn, and α-helix/β-sheet content was higher than that of SBM (p < 0.05). The release rates (k) of AA_LMW in SBM and ESBM were 0.0123 min−1 and 0.0733 min−1, respectively. Enzymatic hydrolysis processing increased the CPfast content of SBM (p < 0.05) and decreased the CPslow and CPresistant contents (p < 0.05). α-helix, β-turn, and the ratio of α-helix to β-sheet were positively correlated with CPfast and k (p < 0.05) and were negatively correlated with CPslow and CPresistant (p < 0.05). β-sheet was negatively correlated with CPfast and k (p < 0.05) and was positively correlated with CPslow and CPresistant (p < 0.05).DiscussionEnzymatic hydrolysis processing altered the digestive dynamics of SBM, increased the CPfast content and the release rate of AA_LMW, which might be attributed to the structure changes of SBM.